FINANCIAL ISSUES OF GREEN ECONOMY DEVELOPMENT (Ustozlar uchun, 2024)
Abstract. This article is devoted to the study of a new direction in economic science called “green” economy. The concept of this term, the main ideas of the direction are revealed. The article examines the current problems arising in the process of interaction between the economy and the natural environment, and also provides various ways to solve them.